Luminescence of Eu3+ in the thin film heterojunction GaAs/SnO2 - Bueno, Cristina de Freitas [UNESP]; Scalvi, Luis Vicente de A. [UNESP]; Li, Maximo Siu; Saeki, Margarida J. [UNESP] (Optical Soc Amer, 2015)
Eu3+ doped tin dioxide (SnO2) thin films are deposited by the sol-gel- dip-coating process on top of GaAs films, which is deposited by resistive evaporation on glass substrate. This heterojunction assembly leads to interesting luminescent emission from the rare-earth ion, unlike the SnO2 deposition directly on a glass substrate, where the Eu3+ transitions are absent. In the heterojunction, the Eu3+ transitions are clearly identified and are similar to emission from samples in the form of pressed powder (pellets), thermally treated at much higher temperatures. However, in the form of films, the Eu emission comes along a broad band, located at higher energy compared to Eu3+ transitions. This broad band is blue shifted as the thermal annealing temperature as well as the crystallite size increase. Although the size of nanocrystallites points toward quantum confinement, another cause of the detected broad band is more feasible: the electron transfer between oxygen vacancies, originated from the disorder in the material, and trivalent rare-earth ions, which present acceptor-like character in this matrix. This electron transfer may relax for higher temperatures in the case of pellets, and the broad band is eliminated.